NEW DATA ON FORMATION CONDITIONS AND COMPOSITION OF ORE-FORMING FLUIDS IN THE PROMEZHUTOCHNOE GOLD-SILVER DEPOSIT (CENTRAL CHUKOTKA, RUSSIA) - Volkov A.V.; Prokof'ev V.Y.; Sidorov A.A. (My University, 2006)
According to the conventional concept based on a great body of empirical data, volcanogenic or epithermal deposits do not grade into mesothermal or plutonogenic ones with depth. However, in the Maisk ore group of central Chukotka, epithermal Promezhutochnoe (Northeast), Sil’noe, and Sopka Rudnaya gold–silver deposits have been discovered in terrigenous flysch sequences at the basement of the Okhotsk–Chukot volcanogenic belt (OCVB).
Keywords: Promezhutochnoe deposit; Chukotka